IMPLEMENTASI PEMBERIAN AIR SUSU IBU SELAMA WAKTU KERJA DI INSTANSI TEMPAT KERJA DI KOTA KEDIRI - MARIA, IIS (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
The exclusive breastfeeding prevalence in Kediri still low because most of the mothers are women workers. Meanwhile, state policy for breastfeeding during working hours in the workplace for working women is only a recomendation of the city major and 2008’s Decree of 3 ministries. The purpose of this study is to explain the implementation of breastfeeding during working hours in the workplace in Kediri.This research was a qualitative research, on 6 workplaces in Kediri. There were 6 leaders/managers as main informants and 25 breastfeeding working women as triangulation informants. Data were obtained through indepth interview, and focus group discussion. The data were analyzed with content analysis method.The results showed that implementation breastfeeding during working hours in the workplace in Kediri has not been implemented well. The workplaces have no lactation room and did not support breastfeeding during working hours at the workplace. There was only one workplace which started to build a lactation room. Communications was only done in one direction from the had to the subordinate. All workplaces have no funding for breastfeeding implementation during working hours at workplace.It is concluded that breastfeeding during working hours at workplace has not been implemented as the 2008’s decree of 3 Ministries. It is suggested for Kediri local government to develop regulation on breastfeeding during working hours in the workplace.Keywords: Implementation, breastfeeding, working hours, workplace, managers